Marsdenia calichicola (Apocynaceae), a narrow endemic, endangered new species from the Mexican Yucatan Peninsula - Carnevali, Germán; Trejo-Torres, Jorge Carlos; Juárez-Jaimes, Verónica; Duno, Rodrigo; Tapia-Muñoz, José Luis; Ramírez-Morillo, Ivón M.; Cetzal-Ix, William (Phytotaxa, 2016)
Marsdenia (Apocynaceae: Asclepiadoideae, Marsdeniae) is represented by five species in the Mexican Yucatan Peninsula (vs. seven in the whole of the province), one of which is herein proposed as new to science.  The new species, Mardenia calichicola Carnevali & Juárez-Jaimes, is only known from a narrow strip of sub-xerophytic forests over calcareous, rocky soils along the northwestern edge in the Yucatán state of Mexico. Marsdenia calichicola is morphologically similar and likely related to M. gallardoae and M. trivirgulata. Among other characters, it differs from Marsdenia gallardoae by the presence of a corona composed of cushion-like calli (corolla lacking calli in M. gallardoae) whereas M. trivirgulata has a glabrous or glabrescent corolla (vs. pubescent in M. calichicola); additional characters are herein discussed. We provide pertinent iconography to aid in the identification of the new species plus a key to diagnose the three species in the M. trivirgulata complex. The conservation status of the new taxon is assessed against the IUCN criteria as CR. A distribution map and a key to the species of Marsdenia from the Yucatan Peninsula Biotic Province are presented.